Jumper's knee. Review of the literature - Fredberg, U.; Bolvig, L. (Scandinavian Journal of Medicine & Science in Sports, 1999)
Jumper's knee is an overuse disease. The initial subjective complaints are well-localized pain, usually occurring after physical activities and often at the lower pole of the patella. The diagnosis of jumper's knee is usually easily established after acquiring a detailed history and a carefully performed physical examination, but the lesion can be mistaken for other disorders or injuries, such as bursitis, meniscal injuries or chondromalacia (1) or other causes of the patellofemoral pain syndrome. Today ultrasonography is the method of choice for the evaluation of jumper's knee as it is both time and cost saving, non-invasive, repeatable, accurate and allows a dynamic image of the tendon, guided injections and control of treatment. Conservative therapy is the treatment of choice in the early stages and includes adequate warm-up, stretching of the quadriceps muscle and physical activity with respect to the pain, and ice pack application after activity. When the pain disappears, the training intensity can be increased. NSAID (Non-Steroidal Anti-Inflammatory Drugs) and local peritendinous injections with long-acting steroids can be a helpful and safe adjuvant to the conservative treatment and should be tried before surgery. Surgical treatment is indicated only if a prolonged and well-supervised conservative treatment program fails in chronic jumper's knee (including local injection with steroid) or in acute total rupture. Review papers concerning jumper's knee are already published (2-5), but in this review the importance of ultrasonography to make the diagnosis, to plan therapy and control the treatment and the safety of peritendinous injection with steroid is pointed out. The scientific documentation for the recommanded treatment (conservative, steroid injection and operation) is, however, insufficient. Many more controlled studies are needed. Ultrasonography and placebo-controlled, double-blinded, cross-over studies for treatment with local injection of steroid are ongoing (6, 7). Scand J Med Sci Sports 1999 Apr;9(2):66-73